Anion polarizabilities in oxynitride glasses. Establishing a common optical basicity scale. Issue 17 (22nd April 2020) - Möncke, Doris; Ali, Sharafat; Jonson, Bo; Kamitsos, Efstratios I.
Abstract : For oxynitrides, oxygen and nitrogen polarizabilities were separated. The optical basicity of the isoelectronic anions F − :O 2− :N 3− varies as follows: Λ (MF m ) = 1/2 Λ (M2 O m ) = 1/3 Λ (M3 N m ). Abstract : Inspired by the work of John Duffy on optical basicity of oxyfluoride glasses, we apply here the concept of optical basicity to oxynitride systems. While in the original work of Duffy and Ingram the basicity of a medium could be probed by s 2 ions like Pb 2+, the low energy intrinsic absorption edge of nitride-containing systems does not allow the use of such probe ions. This study uses therefore experimental data on refractive index and density of alkaline earth and rare earth containing silicate oxynitride glasses, prepared by the authors or taken from the literature. In addition, literature reports on experimental or calculated refractive index, density and polarizability data are used to compare pure nitride systems, e.g. bulk or thin film materials that are either crystalline or glassy. We compare simple and complex nitride systems with their oxygen counterparts, by calculating their optical basicity using the chemical composition as well as the established relationship between optical basicity, Λ, and electronic polarizability in oxide systems. Our results on oxynitride systems are in good agreement with Duffy's previous work on oxyfluoride glasses and indicate that the optical basicity varies for the isoelectronic anions in nitrides, oxides and fluorides (N 3− :O 2− :F − ) of a cation M m + as follows: Λ (MF m ) = 1/2 Λ (M2 O m ) = 1/3 Λ (M3 N m ). Using this relation for CaO, for which the optical basicity was set as unity by Duffy and Ingram, one has Λ (CaF2 ) = 0.50, Λ (CaO) = 1.00 and Λ (Ca3 N2 ) = 1.50. The optical basicity of complex nitrides can therefore be calculated by the same method established for oxides using the equivalent fractions and the basicity of the constituent nitrides. The relationship between nitride polarizability α N and basicity Λ (nitride) was found to be linear, with Λ (nitride) = 0.39 α N − 0.14 where α N is given in Å 3 .